Laser Scanning Ship Hulls to Support Hydrodynamic Simulations - Lovas, Tamás; Somogyi, Árpád József; Simongáti, Győző (Periodica Polytechnica Civil Engineering, 2022)
Terrestrial laser scanning is an effective technology to capture high density and accurate point clouds about objects with complex geometry. Ship industry requires 3D hull models for multiple reverse engineering purposes; renovation, as-built analysis, simulations etc. The paper discusses how terrestrial laser scanning can be applied to capture ship hull geometry to support hydrodynamic simulations. It presents recommendations of survey geometry and methods considering scanner locations, reflectivity issues. Hydrodynamic simulations require specific types of surface models as inputs; data processing procedure is discussed how the point clouds are effectively transformed to models to be applied. Resource analysis is also included, such as duration of survey and processing, equipment to be used.